17 The Efficacy Of The Use Of Manual Therapy In The Management Of Tendinopathy: A Systematic Review. (5th September 2014) - Bennett, Andrew; Watson, Tim; Simmonds, Jane
Abstract : Introduction: Manual therapies have been advocated for the management of tendinopathy. Purpose of the study To systematically review the literature to determine the efficacy of the use manual therapies in the management of tendinopathy. Methods: The review followed a 2 phase process. Phase 1 involved a systematic scoping search of the literature to determine which manual therapy techniques were reported to be efficacious and whether this new review was justified. The criteria to determine those studies eligible for inclusion were thus broad in nature and wide in scope Both non-experimental and experimental studies were eligible. CENTRAL, MEDLINE, EMBASE, PUBMED, AMED, CINAHL, Index of Chiropractic Literature, MANTIS, PEDro, SPORTDiscuss, ISI Web of Science, SCOPUS, HMIC, OpenSIGLE and ZETOC were searched. Keywords related to tendinopathy and manual therapy were used. A further search of the contents pages of key journals, electronic full text journals, conference abstracts and reference bibliographies was also undertaken. In phase 2 the specificity and sensitivity of the eligibility criteria was refined to identify those experimental studies that investigated the therapeutic efficacy of manual therapy specifically. Data derived from these studies was critically analysed. Methodological quality of the included studies was assessed using the PEDro scale for randomised controlled trials and the Modified Downs and Black Quality Index for non-randomised studies. Results: No previous systematic review encapsulating this topic was identified. 22 non-experimental case studies reported the efficacious use of a wide variety of manual therapy techniques for the management of a variety of symptomatic tendons affecting both the upper and lower limb. These techniques can be categorised based on the method of application. "Direct" techniques are applied. directly the tendinopathic tissue. "Local" techniques are applied articular and/or soft tissues within the affected limb. "Spinal" techniques are applied to the motion segments of the spinal column. Following phase 1, 50 experimental studies were identified which used a wide variety of different direct, local and spinal techniques as part of mulitmodal interventions for the management of tendinopathy affecting both the upper and lower limb. Eleven of these studies were eligible for narrative analysis following phase 2. The internal validity of the conclusions derived from these 11 studies was limited by inadequacies with sample size calculation, randomisation, blinding, and of control of both attrition bias and baseline comparability to a varied extent. Nine investigated the use of manual therapy for the management of lateral epicondylalgia and 2 for patella tendinopathy. Analysis revealed tenuous evidence to support the efficacy of the use of "local" manual therapy applied to articular structures in the upper limb, or "spinal" techniques applied to the cervical spine, for the management of lateral epicondylalgia only. Conclusion: Despite extensive anecdotal evidence for use in clinical practice, there is minimal experimental evidence to support the efficacy of the use of manual therapy for the management tendinopathy. The conclusion reflects the lack of high quality experimental evidence published investigating efficacy. Implications for clinical practice: Predominately informed by case study findings it appears reasonable to trial manual therapy in concurrence with other physical therapies. Choice of technique should be informed by the nature of a clinicians skill set, the nature of the patient's presentation and whether the clinical environment allows for sufficient frequency and regularity of treatment. Further experimental research is required of sufficient methodological rigour to fully determine whether manual therapy techniques are efficacious to augment the physical management of tendinopathic conditions.